2017
DOI: 10.3233/jbr-170150
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol characterization of three varieties of Blackberry fruits (Rubus adenotrichos), cultivated in Costa Rica

Abstract: BACKGROUND: Blackberries (Rubus spp.) are fruits rich in secondary components (anthocyanins, proanthocyanidins, phenolic acids, carotenoids and others), recognized for their health benefits. OBJECTIVE: To evaluate the content of different types of phenolic compounds and their antioxidant activity in several extracts of three varieties of blackberry fruit (Rubus adenotrichos) (red thorned, thornless and sweet), using different blackberry standards. METHODS:The varieties of blackberry fruit were analyzed in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
9
0
5
Order By: Relevance
“…From GFS to RPS of Hull, the content of cyanidin-3 -O- glucoside increased rapidly from 5.52 to 507.67, which was significantly higher than that of the other anthocyanin fractions. Previous studies also confirmed that the content of cyanidin-3 -O- glucoside increased significantly in the process of blackberry from green fruit to ripening, and was the main component of anthocyanin in blackberry fruit [ 28 ]. With the growth of fruit, the content of anthocyanin fractions increased significantly.…”
Section: Resultsmentioning
confidence: 61%
“…From GFS to RPS of Hull, the content of cyanidin-3 -O- glucoside increased rapidly from 5.52 to 507.67, which was significantly higher than that of the other anthocyanin fractions. Previous studies also confirmed that the content of cyanidin-3 -O- glucoside increased significantly in the process of blackberry from green fruit to ripening, and was the main component of anthocyanin in blackberry fruit [ 28 ]. With the growth of fruit, the content of anthocyanin fractions increased significantly.…”
Section: Resultsmentioning
confidence: 61%
“… Cluster distribution of proanthocyanidins based on the total proanthocyanidin content within plant families and according to previously published data [ 96 , 97 , 99 , 100 , 101 , 102 , 104 , 105 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 ]. Euclidean distances were calculated with the average linkage method.…”
Section: Figurementioning
confidence: 99%
“…Myrtle pigmented berries are a good anthocyanin source, and particularly 'Giovanna' showed the highest concentration. Some authors indicated an anthocyanin content of 8.4-41.1 mg C3G/g DW in haskap berries [52], 15.4 mg of cyanidin in the cultivar 'Red thorn' of blackberry at ripe stage [53], and 14.5 mg of cyanidin in rabbiteye blueberry fresh berries [54].…”
Section: Differences In Phenolic Compounds Determined By Biological D...mentioning
confidence: 99%